Active Learning and Teacher Training: Lesson Study and Professional Learning Communities - Ishii, Kyoko (Scientia in educatione, 2017)
Active learning is an innovation of teaching and learning and strongly connected to teacher education reform. A teacher’s role in a knowledge-based society is being shifted from a knowledge teller to a facilitator. It is diï¬cult to shift a teacher’s perspective from “how to teach” to “how students learn.” However, through a collaborative lesson study, teachers can discuss students’ learning in a classroom. The university can function as a facilitator to cultivate a professional learning community. This paper discusses the practice of active learning in teacher training at the University of Fukui in Japan. The faculty provides active learning for prospective teachers to engage collaboratively in scientiﬁc inquiry using physics by inquiry. Based on the viewpoint that teacher development is a continuous, lifelong process, and the teacher is a reï¬ective practitioner, teacher training should also be an active, lifelong endeavor. Moreover, the system and structure of the lesson study and collaborative reï¬ection promote a professional learning community. Both pre-service and in-service teachers develop pedagogical content knowledge through repeated practice and reï¬ection.